Effect of Admixture on the Hydraulic Conductivity of Compacted Loess: A Case Study - Pan Liu; Xuejiao Zhang; Min Zhang; Xueqiang Yang (Advances in Civil Engineering)
Hydraulic characteristic of the exposed ground plays an important role in the construction of “sponge city,” which is a popular concept in the world recently. Loess soil, which is a common geomaterial in its distribution area approximately 9.3% of the world’s land surface, usually could not satisfy the engineering requirement only by compacting without any other treatments. This paper aims to investigate the effect of a natural geomaterial, lateritic soil, which is more economical and environmental than the traditional admixtures such as cement and lime, on the saturated hydraulic conductivity (ksat) of compacted loess. A series of falling-head permeability tests on pure loess and lime-treated loess were carried out firstly for comparison; then lime-treated loess mixed with different contents of lateritic soil was tested. To verify the availability of the coverage of high density lateritic soil on pure loess for antipermeability, which is a common treatment in local area, tests of different thickness of the coverage were conducted. The test results revealed that the admixture of lime could obviously decrease ksat of pure loess and 3% might be the most economical content. An empirical algorithm was proposed based on the results to estimate ksat of lime-treated loess of which the lime content is out of the scope studied in this paper, and it would be useful for engineering design and numerical simulation of safety evaluation. The addition of lateritic soil in the 3% lime-treated loess could further decrease ksat and its performance for antipermeability was better than increasing the lime contents simply. The coverage of high density lateritic soil could also improve the antipermeability of loess, and thickness at least of 30 mm was suggested for engineering practice.